CONSEQUENCES OF THE CADMIUM CONTAMINATION FOR THE PHYSICAL AND CHEMICAL STATUS OF THE DARK GRAY PODZOLIC SOIL IN THE WESTERN FOREST-STEPPE OF UKRAINE - Kachmar, N.; Datsko, T.; Ivankiv, M.; Dydiv, A.; Panasiuk, R. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
Contamination with heavy metals is a major concern because of their toxicity and threat to human life and environment. The object of the study was dark gray podzolic soil polluted with cadmium. The samples were taken from the research field of Lviv National Environmental University, from the layer of 0–60 cm deep. Cadmium (CdCl2·2.5 H2O) was applied to the top layer of soil as water-salt solutions in different doses, namely 0; 3; 15; 30 mg kg-1. The basic chemical and physical properties, such as soil reaction, organic carbon content, grain size composition, total surface area, porosity, and hydrolytic acidity of the samples were analyzed using routine laboratory procedures. The soluble forms of Cd were also investigated. The soil reaction ranged between 6.9 and 7.6 in 1M KCl and 7.4–8.1 in H2O, whereas the content of organic C ranged between 0.62 and 1.59 %. For Cd-treated samples, the content of sand fraction changed from 7 to 25 %, silt fraction – from 47 to 63 %, and clay – from 18 to 43 %. The pore volume of polluted soil ranged from 411 to 515 mm3 g-1. The total surface area of the soils varied from 26.8 m2 g-1 to 40.0 m2 g-1. The content of available forms of cadmium was the highest in the top layers of soils. The presence of this element was similar to that in the control sample at the depth of 30 cm only for small initial doses of Cd. The content of Cd for the highest dose and at the deepest soil level was higher than for the control sample. The behaviour of cadmium in soil and the influence of cadmium on the basic characteristics of dark gray podzolic soil can be caused by the chemical properties of this metal and the properties of the soil. The rate of migration of mobile forms of cadmium in the soil may be an indication of its self-purification.